Indonesia Strategi Kampanye Politik Partai Nasdem Di Media Instagram Pada Pemilu 2019 - Putri, Bella Triana Cantika; Rahmawati, Restu; Ilmar, Anwar (Indonesian Democracy Research Center, 2023)
Nasdem Party political campaign strategy on Instagram Media in the 2019 Election. The phenomenon of political campaigns is currently colored by the explosion of digital media where digital media is the main stream for direct campaign activities. According to Rise and Paisley Campaign is the desire to influence the beliefs and behavior of others with the appeal of communication. A campaign is a joint effort led by a group of people with the goal of changing certain attitudes and behaviors. This thesis will examine Instagram's online campaign activities as a campaign medium using the case study of the Nasdem Party, because the author is interested in the success of Nasdem which always increases every year, the success carried out by Nasdem is inseparable from the campaign strategy it carries out. This study uses a qualitative approach and the type of research used is explanatory research with the case study method. The theory used is political marketing theory by Kotler and Armstrong, namely the 4p marketing-mix (product, promotion, price and place). as primary research data with the technique of determining informants carried out by purposive sampling. Second, documentation as secondary research data. The research results obtained show that the NasDem Party has succeeded in carrying out a campaign on Social Media Instagram @official_nasdem. By using the 4P campaign strategy, namely Promotion, Price, Place, Product. The success of the NasDem Party's 2019 election campaign on social media Instagram @official_nasdem did not escape obstacles such as bazers, hoaxes, and black campaigns. However, these obstacles did not become a barrier for the @official_nasdem account to continue providing political education, or political outreach through campaign content. which was uploaded.